POTENSI LAHAN SEMPIT MENJADI LAHAN PERTANIAN MENGGUNAKAN TEKNIK VERTIKULTUR DI DESA SENDANGREJO - Pramesti Rajati, AnandayuGaluh; Sitanggang, Indra Gamaliel; Respati, Adam Arinto; Febriyanti, Rina; Anariyah, Ananda Sofiatun; Putranto, Gofar Faza Haryo; Anjani, Nisya Ari; Arifida, Sa’adillah; Sari, Suratna; Hariyanto, Yasmin Zulfa Agustin Alfiyah; Herdiansyah, Ganjar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Sendangrejo Village in Wonogiri District is a community where the majority of residents work as farmers. This activity aims to provide education and training to the community, especially the PKK mothers and the Dawis Group (Dasa Wisma), on utilizing limited land around their homes to produce quality food using Verticulture Planting Techniques. Verticulture can be a solution and an alternative to maximizing the use of limited land around homes, as well as conserving water during the dry season. The method used in this activity is divided into three stages: material presentation, discussion/Q&A, demonstration and hands-on practice, and evaluation. The results of this activity show a positive response from the community regarding land efficiency, water conservation, and improved environmental aesthetics. The community also recognized that utilizing limited land around their homes can increase food production, thereby improving the welfare of the residents of Sendangrejo Village.